The New Year’s fairy - Wurfel, Marlene (My University, 2020)
This largely forgotten but wonderful fairytale is written and rearranged by Marlene Wurfel, based on the concept and story by the American fabulist Emilie Poulsson (1853-1939) Music: “English Country Garden” & “Apline Bierhalle” & “Christmas Homecoming” by Aaron Kenny courtesy YouTube Audio Library Auld Lang Syne (Instrumental) by the Jingle Punks courtesy YouTube Audio Library Sound effect attributions: “Fairy Logo” by DDmyzik courtesy of a Creative Commons Attribution Licence via www.freesound.org https://creativecommons.org/licenses/by-nc/3.0/ “Coagulated” by Timbre & “Champagne Cork Pop” by Ruben Uitenweerde courtesy of a Creative Commons Attribution Licence via www.freesound.org "Fireworks, Close, A (H1).wav" by InspectorJ (www.jshaw.co.uk) of Freesound.org
Keywords: storytelling; children's stories